The Implementation Of Direct Learning Model By Using Props Beads At The Material Operations In Addition And Subtraction Of Integers At The Iva Class In Sd Negeri 002 Tualang - Elita Elita (Fakultas Sastra Universitas Ekasakti, 2018)
Mathematics is a very important lesson so that math needs to be given to all learners starting from elementary school.It aims to equip learners with the ability to think logically, analytically, systematically, critically and creatively as well as the ability to work together.Competence is required for learners have the ability to obtain, manage and utilize information.In line with one of the goals of mathematics in the Education Unit Level Curriculum (SBC) that have properties appreciate the usefulness of mathematics in life is curiosity, concern and interest in studying mathematics, as well as resilient and confident in solving problems. The researchers interested in improving the learning process in order to achieve maximum mathematics learning results with the application of direct learning models that use beads props in the material of addition operation and reduction of integers in class IVA SD Negeri 002 Tualang, the researcher hopes that it can improve student learning outcomes Better. Based on the background stated above, the authors formulate the problem that is: does the application of direct learning model by using beads props can improve mathematics learning outcomes in the material of addition operation and reduction of integers in class IVA SD Negeri 002 Tualang in the even semester of the school year 20 14/20 15? This research took place at SD Negeri 002 Tualang.Implemented in the second semester of the school year 2014/2015.This form of research is collaborative classroom action research.Classroom action research aims to improve or improve the quality of classroom teaching practice (Arikunto et al, 2006).Collaborative classroom action research on this research was carried out by researchers with grade IVA teacher SD Negeri 002 Tualang in a team that simultaneously with the aim of improving the practice of learning.Team relationships are partnerships, so that the teacher's position with the rest of the team is the same to think about the issues to be studied in classroom action research. Based on the results of research and discussion is a fact that the Application of Learning Model Directly on material Operation Count Integer can improve learning outcomes math class student IVA Elementary School 002 Tualang in the second semester of the school year 2014/2015, especially on the subject matter surgery Calculate the integers of the lesson year 2008/2009.